Análise da dinâmica acoplada de uma máquina elétrica rotativa e sua estrutura de suporte - Rocha Junior, Edmilson Bermudes (2004)
It’s performed in this work the dynamics of the analyzes of a system made of a directcurrent electrical unbalanced engine, supported by an elastic structure. This kind ofsystem is seen as an non-ideal system, that is, an interaction between the engineand the electrical system. The importance of the study of problems involving thedocking of dynamics of various systems has increased through the constructivecharacteristics of the machines and its structures. It is believed that the constructivemachines tend to be more flexible and may work in higher rotations as well. Then,some phenomena that were not noticed in other generation machines can beobserved now and the use of a more complete models are necessary to explain it.On the operational side a bigger demand of the control system is made even morenecessary. The set of equations that lead the system studied in this work engine-structure is composed by the mechanical equations resulted from the Lagrangeequations and the ones from the Kirchhoff law tension. Moreover, the Runge-Kuttafivth order is used , with a variable pitch aiming at the simulation system. Finally, theanalyzes of the electrical motor arousal independence and series performance isrealized, taking into account the influence of the structure over the rotation.